Grassroots information divides in China: Theorising everyday information practices in the Global South. (October 2021) - Yan, Pu; Schroeder, Ralph
Highlights: We put forward a more holistic theoretical model of information seeking practices in everyday life. We extend the context to the Global South, where there is less research on mobile platforms. We link the variation in everyday information seeking practices to different groups. We show the relation between information divides and social changes in China and India. We apply a theory of digital divides in everyday information practices to the Global South contexts. Abstract: The internet is becoming a major source of everyday information, yet existing research often focuses on specific information seeking contexts such as health, climate change, news, or hobbies. In this paper, we put forward a more holistic theoretical model of information seeking practices in everyday life that combines the social phenomenological perspective of everyday life information seeking practices and the domestication framework. We extend the cultural context to the Global South countries, where there is less research on "mobile first" societies centred on emerging mobile platforms. Based on extensive and mixed-methods fieldwork in rural and industrial China about everyday information seeking practices, the paper goes beyond previous research about digital divides in internet access and internet literacy. Instead, it focuses on divides in everyday information seeking practices. We argue that new divides are emerging between those with more restricted everyday internet uses and those with broader and more diverse ones. We compare everyday information practices and divides in China with those in India and show how a theory of digital divides in everyday information seeking practices can be applied beyond both countries to the Global South. Such a theory can also contribute to the design of informatisation policies.